Den stædige belgiers kamp - en artikel om 'Bosmandommmen' og konsekvenserne for professionel sportsudøvelse - Pedersen, Nicolai Blom (Forum for Idræt, 1999)
Analyse af den belgiske fodboldspiller Jean-Marc Bosmans sejr over de store fodboldorganisationer ved EF-domstolen og afgørelsens betydning for professionel sportsudøvelse inden for fodboldens verden. The Case of the Stubborn Belgian – The Bosman Case One of the most important issues in recent times for professional soccer and professional sport as a whole has been the Bosman case and verdict. It is a case, which, when it came to a head on December 15th 1995, shook up the world of professional sports. The Belgian soccer-player, Jean-Marc Bosman, had successfully fought and won his case against all of the major soccer associations at the EU courts, and hereby destroyed the former player transfer system. With a description of the principles in the Bosman case, the article will throw light on the central and most important parts of the verdict. In this first part the entire situation that resulted in the lawsuit will be considered. The second part of the article is an analysis of the consequences of the verdict for professional sports, focusing mainly on soccer, where there also will be looked back on the four years that have passed since the verdict. Again the starting point is within the world of soccer, and from here the article will draw parallels to other professional sports.